Novel clinical and molecular findings in Spanish patients with nevoid basal cell carcinoma syndrome. (22nd January 2018) - Alonso, N.; Cañueto, J.; Ciria, S.; Bueno, E.; Palacios‐Alvarez, I.; Alegre, M.; Badenas, C.; Barreiro, A.; Pena, L.; Maldonado, C.; Nespeira‐Jato, M.V.; Peña‐Penabad, C.; et al.
Summary: Nevoid basal cell carcinoma syndrome (NBCCS), also known as Gorlin Syndrome, affects only 1 in 56 000 people. It is usually inherited from a parent with the condition and affects both males and females equally (autosomal dominant inheritance). People with NBCCS may show characteristic features such as extra fingers or toes, irregular ribs, an unusually shaped face and large head. Tumours sometimes develop, particularly jaw cysts and basal cell carcinomas (BCCs) of the skin from which the syndrome is named. NBCCS is caused by mistakes (mutations) in a gene called PTCH1 located on the long arm of chromosome 9. PTCH1 acts as a brake on a set of chemical processes in cells called the Hedgehog (HH)/GLI signalling pathway. In NBCCS, mutations inactivate PTCH1 allowing excessive Hedgehog signalling. This loss of control results in the abnormal bones and tumours. Within an affected family, people with the same genetic mutation can have very different abnormalities. This group from Spain studied 22 unrelated Spanish people with NBCCS to see if they could discern any relationship between specific clinical abnormalities and specific genetic mutations. BCCs were very common, occurring in 96% of patients with 43% having more than 50; 77% had jaw cysts. Two abnormalities had not previously been recognised in NBCCS: double uterus and a benign nerve tumour. They found 19 PTCH1 mutations that had not previously been reported. However, they could not find any pattern relating the type of mutation to the clinical abnormalities. Presumably other factors besides the PTCH1 mutation causes the clinical features. Abstract : Linked Article: Alonso et al. Br J Dermatol 2018; 178 :198–206